SAFETY ASSESSMENT OF AYURVEDIC GOLD MEDICATION SUVARNA BHASMA, IN WISTAR RATS - Abhay N. Kulkarni; Mahalaxmi Mohan
Suvarna bhasma (SB) contains gold and lead, which are highly potent metals and are toxic in their crude form. This study evaluated the safety profile of the medication. Suvarna bhasma was administered for 90 consecutive days orally at three doses (10.23 mg kg-1, 40.92 mg kg-1 and 102.3 mg kg-1 body weight) to wistar rats. Clinical observations, feed and water consumption, and body weight changes were noted during the study period. On the 91st day, hematological, biochemical and histopathological changes were studied. There was a significant decrease in body weight of rats at a low dose (10.23 mg kg-1) at fourth week, which could not be correlated with feed and water consumption findings. Thus, change was not considered as a treatment-related effect. Suvarna bhasma showed no evident untoward effect in haematological, biochemical and histopathological parameters in the 90 day-subchronic toxicity study (OECD 408 guidelines) and was safe in Wistar rats.